The cause of Christian education - Edlin, Richard (Lowa, United States of America Dordt College Press, 2014)
Richard Edlin explores the reasons for and the distinctives of Christian education at the school and higher education levels. This book highlights foundational belief perspectives and shows how these apply in curriculum and related areas such as vision and mission, the place of the Bible, evaluation and assessment, the teacher as mentor, and professional development. It includes a special section for Christians in public school settings. Edlin is a recognized scholar and speaker in the global Christian education community. He writes from a background of 40 years international experience in Christian education. The book, described by a reviewer as a "must read" for anyone involved in Christian education, is an important resource for teachers, pastors, and parents, and also for university/college teacher training courses.
Includes study guide.
Keywords: Christian education, philosophy, curriculum, evaluation, assessment